PENGARUH KOMPETENSI SOSIAL GURU TERHADAP PEMBENTUKAN KARAKTER PEDULI SOSIAL SISWA SMA NEGERI BINAAN KHUSUS KOTA DUMAI - Ivo Lovita Nasrun; Hambali Hambali; Separen Separen (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract This research set on teachers’ social competence and social care character building in students of SMAN Binsus Dumai. The formulated research problem mentioned “how is the effect of teachers’ social competence on social care character building in students of SMAN Binsus Dumai”. This research sought to find out the effect of teachers’ social competence on social care character building in students of SMAN Binsus Dumai. The practical benefit for researchers is to increase knowledge and understanding of the world of education, leading to more enthusiastic participation at schools. The research population included eleventh grade students, totaling 200 students. The research samples were 50 students selected through the Proportional Random Sampling. Research data were collected by means of questionnaires, observations, interviews, and document studies. The data were then analyzed using a simple linear regression formula, assisted by SPSS version 16 application. The proposed hypothesis stated that there is an effect of teachers’ social competence and social care character building in students of SMAN Binsus Dumai. The results revealed that there is a significant effect of teachers’ social competence on social care character building in students of SMAN Binsus Dumai by 36.6%.Keywords: Effect, Teachers’ Social Competence, Students’ Social Care Character